Antibacterial Effect Of Curcuminoid Silica Nanoparticle To Escherichia Coli Bacteria - Hendrawan, Bobby; Novita, Bernadette D; Hendrata, Adi P (JOURNAL OF WIDYA MEDIKA JUNIOR, 2019)
Background: Escherichia coli is one of the main bacteria that cause urinary tract infection. In the past few years, Escherichia coli’s susceptibility to antibiotic has been decreased and causing antibiotic resistance. Furthermore, Curcuma longa plant has been used daily by the population as a cooking spice, and evidently has an antibacterial effect on some bacteria such as Staphylococcus aureus, Klebsiella pneumoniae, and Escherichia coli. Curcumin as the active ingredients of Curcuma longa has a low water solubility and poor absorption so that silica nanoparticle usage will help the solubility and absorption problem of Curcumin. Aim: This study aimed to know the antibacterial effect of Curcuminoid silica nanoparticles to Escherichia coli. Methods: This research is an in vitro experimental study and checking by using a microdilution method and observed with a spectrophotometer. Results: There is 60,6% inhibition obtained at 1000 μg/mL. MIC and MBC were not obtained at 62,5 μg/mL to 32000 μg/mL. Conclusion: Curcuminoid silica nanoparticles has no antibacterial effect against Escherichia coli.